Integrating Supported Education and Supported Employment for People with Mental Illness: A Pilot Study - Rudnick, Abraham (International Journal of Psychosocial Rehabilitation, 2014)
Background: Supported employment is an evidence based practice for people with mental illness, but it does not typically achieve skilled work. Such achievement may be achieved if supported employment is integrated with supported education. Objective: This exploratory study evaluated the first year of an innovative program integrating supported employment with supported college education for 37 college students with mental illness. Method: A phenomenological evaluation methodology was used. A purposive sample of 6 participating students with mental illness (schizoaffective disorder, bipolar disorder, and major depression) and 5 of their significant others, as well as 4 of their counselors from the collaborating organizations, were interviewed at 3 points in time. Thematic analysis was conducted on the qualitative data. Results: Thematic analysis of interview data indicated satisfaction with the program and other promising outcomes. Conclusion: Integrating supported postsecondary education and supported employment for individuals with mental illness is promising.